Effect of Cu Addition on the Electrochemical Corrosion Performance of Ni3Al in 1.0 M H2SO4. (23rd June 2015) - Porcayo-Calderon, J.; Rodriguez-Diaz, R. A.; Porcayo-Palafox, E.; Colin, J.; Molina-Ocampo, A.; Martinez-Gomez, L.
Abstract : The effect of Cu addition on the electrochemical corrosion behavior of Ni3 Al intermetallic alloy was investigated by potentiodynamic polarization, open-circuit potential, linear polarization resistance, and electrochemical impedance spectroscopy in 1.0 M H2 SO4 solution. Performance of the pure elements (Cu, Ni, and Al) was also evaluated. In general, Cu addition improved the corrosion resistance of Ni3 Al. Electrochemical measurements show that corrosion resistance of Ni3 Al-1Cu alloy is lower than that of other intermetallic alloys and pure elements (Ni, Cu, and Al) in 1.0 M H2 SO4 solution at 25°C. Surface analysis showed that the Ni3 Al alloys are attacked mainly through the dendritic phases, and Cu addition suppresses the density of dendritic phases.